RAKYAT DALAM BINGKAI BUDAYA POLITIK KONTEMPORER - Dewi Sad Tanti (Universitas Mercu Buana, 2014)
Each political party or figure Indonesian leader of the party or non- partyrepresents the interests of diverse nature. The condition is triggered by the polarization of thepolitical parties with different ideological background , programs , and offer alignments tothe people. The interesting thing , every action figure Indonesian leaders are constantlybehalf of the people . The issue is where the real people are represented by political partiesin Indonesia ? Is alignments framework prominent leader of the dominant or only limitedmobilization articulate the needs of real people ? By using social semiotic analysis , the studyoutlines the cultural meaning action figures leaders of Indonesia on behalf of the people andthe establishment of contemporary political culture in the cover photo to see their Facebooksocial mediaSetiap partai politik atau tokoh pemimpin Indonesia dari partai atau non partaimewakili berbagai kepentingan yang beraneka ragam. Kondisi itu dipicu oleh polarisasipartai-partai politik dengan aneka latar ideologi, program, dan tawaran keberpihakan kepadarakyat. Hal yang menarik, setiap aksi tokoh pemimpin Indonesia tersebut senantiasamengatasnamakan rakyat. Persoalannya rakyat mana sesungguhnya yang diwakili oleh partaipolitik yang ada di Indonesia? Apakah kerangka keberpihakan tokoh pemimpin dominanhanya sebatas mobilisasi ataukah mengartikulasikan kepentingan rakyat sesungguhnya?Dengan menggunakan analisis semiotik sosial, kajian ini mencoba menjabarkan maknakultural aksi para tokoh pemimpin Indonesia yang mengatasnamakan rakyat danpembentukan budaya politik kontemporer di tampilan foto sampul media sosial Facebookmereka.